Efek Kompensasi, Motivasi, Budaya Organisasi dan Komitmen Organisasi terhadap Organizational Citizenship Behavior - Badaruddin Badaruddin (STIE Amkop Makassar, 2022)
The purpose of this study was to determine the effect of compensation, motivation, organizational culture and organizational commitment on organizational citizen behavior (OCB) on the employees of PT Fajar Graha Pena Makassar's leadership. The results of this study are expected to be a reference for further researchers in the field of human resource management studies, especially employee organizational citizenship behavior (OCB). The approach in this study is a quantitative approach because this research is presented with numbers. The population in this study were employees of PT. Fajar Graha Pena Makassar as many as 123 employees. The sampling technique is purposive sampling by selecting the operations section and the administration section where the operations section is 23 people and the administration section is 15 people. So the total sample is 38 people. The data collection method used in this study is a questionnaire method, namely by distributing a list of questions (questionnaires) and referring to research variables. Then, the data analysis method used in this study is multiple linear regression analysis.. The results of the study found that compensation has a positive and significant effect on employee organizational citizen behavior (OCB); motivation has a positive and significant effect on employee organizational citizen behavior (OCB); Organizational culture has a positive and significant effect on employee organizational citizen behavior (OCB) and organizational commitment has a positive but not significant effect on employee organizational citizen behavior (OCB).